Digital Transformation of Islamic Boarding School Microfinance Institutions in Reducing Consumptive Behavior of Students (Santri) - Moh. Suhud; Nikmatul Masruroh; Babun Suharto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In the modern era, there has been a shift in consumption behavior among students in Islamic boarding schools (santri). Santri, who are traditionally expected to practice simple consumption habits, are now learning towards excessiveness, and even tendencies toward hedonism due to modernization. This often leaves parents struggling to meet their children’s consumption needs, particularly their wants. Therefore, this study aims to first, explore the traditional consumption habits of santri; second, analyze the shifts in their consumption behavior; and third, examine the presence of digital transformation in Islamic boarding schools as a means to curb santri’s consumptive behavior. This research employs a qualitative approach, specifically a case study method. The subjects were selected through purposive sampling, and data were collected through observation, interviews, and documentation. Data analysis was conducted using the interpretive technique within the interactive model by Miles and Huberman. Data validity was ensured through source triangulation and technique triangulation. The study yielded the following results: First, santri have traditional consumption practices, prioritizing halal and thayyib (pure and good) products, simplicity, and a sense of community. Second, modernization has shifted santri’s consumption habits towards a more hedonistic approach, favoring instant goods and trendy products, thereby increasing their financial dependence on parental support. Third, Islamic boarding schools have partnered with various institutions to curb this consumptive behavior. Digital transformation has been implemented to improve spending efficiency among santri and facilitate the monitoring of their financial management.